PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES DENGAN MEDIA VIDEO PEMANFAATAN SUMBER DAYA ALAM UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR IPS SISWA KELAS VIII C SMP NEGERI 1 SRAGEN TAHUN PELAJARAN 2014/2015 - S., Sumarno; Suryani, Nunuk; Joebagio, Hermanu (Sebelas Maret University (UNS), 2015)
Examples non examples cooperative learning type is a learning model with pictures to be analysized by the students and the students can procedure a brief description from the material with examples and non examples. The purpose of this research is to determine: the implementation of cooperative learning examples non examples model using natural resources video to improve the creativity and students’ achievement on IPS in VIII C, SMP Negeri 1 Sragen.This research is the Classroom Action Research which concist of three cycle. These cyclus have three steps namely planning, implementation, observation and reflection. This subject of this research is class VIII C SMP Negeri 1 Sragen which concist of 34 students. The tehniques of collecting data uses test, observation, documentation and field notes. Data analysis uses descriptive qualitative analysis. The result shows that the questionares given to the students on cycle one can be found that the average score is 62.50 and minimal criteria is 47.06%, cycle two the average score is 64.85 and minimal criteria is 79.41%, cycle three the average score is 67.03 and minimal criteria is 94.12%. And the post test show that the average score on cycle one is 69.26(2.77) and the achievement of minimal criteria is 47.06%, the average score on cycle two is 78.38(3.14) and the achievement of minimal criteria 79.41%, the average score on cycle three 84.00(3.35) and the achievement of minimal criteria is 100%. The Implementation of cooperative learning examples non examples model using natural resources video can improve the students’ creativity and achievement because this model give the chances to the students to think critically on the theme and the students can find the concept directly from the analysis. The students involve in discovery learning process which support the students to build the concept progresivelly through to the experience from examples non examples. This learning model is suitable for the theme using natural resources. Show, based on the results above can be concluded that the implementation of cooperative learning examples non examples model using natural resources video can improve the creativity and students’ achievement on IPS in VIII C SMP Negeri 1 Sragen.